Teleost innate immunity, an intricate game between immune cells and parasites of fish organs: who wins, who loses - Sayyaf Dezfuli, Bahram; Lorenzoni, Massimo; Carosi, Antonella; Giari, Luisa; Bosi, Giampaolo (Frontiers in Immunology, 2023)
Fish, comprising over 27,000 species, represent the oldest vertebrate group and possess both innate and adaptive immune systems. The susceptibility of most wild fish to parasitic infections and related diseases is well-established. Among all vertebrates, the digestive tract creates a remarkably favorable and nutrient-rich environment, which, in turn, renders it susceptible to microparasites and macroparasites. Consequently, metazoan parasites emerge as important disease agents, impacting both wild and farmed fish and resulting in substantial economic losses. Given their status as pathogenic organisms, these parasites warrant considerable attention. Helminths, a general term encompassing worms, constitute one of the most important groups of metazoan parasites in fish. This group includes various species of platyhelminthes (digeneans, cestodes), nematodes, and acanthocephalans. In addition, myxozoans, microscopic metazoan endoparasites, are found in waterdwelling invertebrates and vertebrate hosts. It is worth noting that several innate immune cells within the fish alimentary canal and certain visceral organs (e.g., liver, spleen, and gonads) play active roles in the immune response against parasites. These immune cells include macrophages, neutrophils, This is a provisional file, not the final typeset article rodlet cells, and mast cells also known as eosinophilic granular cells (EGCs). At the site of intestinal infection, helminths often impact mucous cells number and alter mucus composition. This paper presents an overview of the state of the art on the occurrence and characteristics of innate immune cells in the digestive tract and other visceral organs in different fish-parasite systems. The data, coming especially from studies employed immunohistochemical, histopathological, and ultrastructural analyses, provide evidence supporting the involvement of teleost innate immune cells in modulating inflammatory responses to metazoan and protozoan parasitic infections.